An Analysis of Compensation Techniques for Translation Loss and Captioning Guidelines in Merantau Subtitle - Yanriski Stiasih (Passage, 2013)
This study focuses on the translation and captioning techniques which are applied in the English Subtitle of Merantau film. Drawing on Hervey and Higgins’ (1992) concept of compensation techniques and Karamitroglou’s (1998) captioning guidelines, the study finds that the translator mostly uses Compensation in Kind technique to compensate for the translation loss. This choice may be due to the translator’s ability to find the equal expression in target language that is more acceptable. It is also found that the translated script has fulfilled the standards of captioning. Keywords: Compensation Techniques, Translation Loss, Captioning, Equal Expression